Investigation of prognostic indicators for human uveal melanoma as biomarkers of canine uveal melanoma metastasis. (28th October 2013) - Malho, P.; Dunn, K.; Donaldson, D.; Dubielzig, R. R.; Birand, Z.; Starkey, M.
Abstract : Objective: To evaluate if 14 genes that discriminate metastasising and non‐metastasising human uveal melanomas can differentiate metastasising and non‐metastasising uveal melanomas in dogs. Methods: Nineteen archival biopsies of eyes with a histopathological classification of primary benign (n = 9) and malignant (n = 10) uveal melanoma were selected. Thoracic and/or abdominal metastases confirmed metastatic spread of the primary tumour in seven dogs during the follow‐up period. Gene expression was assayed by Reverse Transcription‐quantitative Polymerase Chain Reaction. Genes displaying statistically significant differences in expression between the metastasising and non‐metastasising tumours were identified. Results: Four genes (HTR2B, FXR1, LTA4H and CDH1) demonstrated increased expression in the metastasising uveal melanomas. Clinical Significance: This preliminary study illustrates the potential utility of gene expression markers for predicting canine uveal melanoma metastasis. The genes displaying elevated expression in the metastasising tumours are part of a 12‐discriminating gene set used in a routine assay, performed on fine needle aspirate biopsies collected without enucleation, for predicting human uveal melanoma metastasis. Further work is required to validate the results.